WARISAN TANAH AKIBAT PERKAWINAN CAMPURAN DALAM PERSPEKTIF HUKUM POSITIF INDONESIA - Nugraha, Riko (Tribuere, 2024)
This article examines the legal consequences of land ownership rights for heirs born from mixed marriages between Indonesian citizens and foreign nationals within the framework of Indonesia’s positive law. The study focuses on the issue of limited dual citizenship held by children from mixed marriages and its implications for inherited land ownership. According to the Basic Agrarian Law No. 5 of 1960, land ownership rights can only be held by Indonesian citizens; thus, a child who opts for foreign citizenship must relinquish such rights within a specified period. This research explores the overlap between agrarian law, citizenship law, and inheritance law, and compares it with Australia’s more flexible legal approach to foreign land ownership. Findings reveal that while Indonesia’s nationality-based land ownership restrictions aim to safeguard agrarian sovereignty, they may result in legal inequities for children of mixed marriages. The study recommends regulatory reform to provide legal certainty and protect inheritance rights without undermining the principle of nationalism.